THE IMPACT OF STUDENT ASSISTANTS ON INTERACTIVE ENGLISH LEARNING ENVIRONMENTS - Shohib, Jinani Firdausiyyah; Robiah, Maulidia Habibatur; Aldama, Putri Anggun Nur Imamah Ulfa (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2025)
Glossophobia, the fear of public speaking, is a widespread problem among students, often impacting their academic success and personal growth. This fear can make it difficult for students to engage in class discussions or presentations. Fortunately, technology offers a variety of tools to help reduce glossophobia and improve speaking skills. Technologies such as language learning apps, virtual reality (VR), and speech recognition software allow students to practice speaking in low-pressure environments, which can help them build confidence. This article explores the role of these technological tools in helping students overcome their fear of public speaking and improve their speaking abilities. The study also presents data on the effectiveness of these technologies and their practical application in real-world learning settings. By leveraging technology, students can practice and refine their speaking skills, which can help them become more confident and proficient public speakers. This research highlights how such tools are making a positive impact on students' public speaking skills and overcoming glossophobia.